Surgical management of a rapidly growing chest wall mass of the neonate - Danny Lascano; Michael J. Zobel; Abigail K. Zamora; Murad Alturkustani; Shengmei Zhou; Eugene S. Kim (Elsevier, 2021)
A two-week-old infant male presented with an asymptomatic large left-sided chest wall mass. On physical exam, an approximately 3 cm firm, non-mobile mass was palpated in the upper left lateral chest wall. A chest radiograph and computed tomographic scan demonstrated a 5 cm mass of the chest wall with erosion and deformity of the left 5th and 6th ribs. An initial plan of non-operative management and close observation was employed, given the mass's benign appearance on imaging. However, after six weeks, the mass was noted to markedly increase in size, particularly the intrathoracic portion with compression of the underlying lung. An open surgical biopsy was performed with a frozen section, which suggested a mesenchymal hamartoma, and en bloc surgical resection was performed with GORE-TEX® patch reconstruction. After an uneventful postoperative course, the infant was discharged home and is doing well 12 months after surgery. The pre-operative and operative management considerations of chest wall masses of the neonate are discussed.